2013
DOI: 10.1186/2050-7283-1-5
|View full text |Cite
|
Sign up to set email alerts
|

A rasch model to test the cross-cultural validity in the positive and negative syndrome scale (PANSS) across six geo-cultural groups

Abstract: BackgroundThe objective of this study was to examine the cross-cultural differences of the PANSS across six geo-cultural regions. The specific aims are (1) to examine measurement properties of the PANSS; and (2) to examine how each of the 30 items function across geo-cultural regions.MethodsData was obtained for 1,169 raters from 6 different regions: Eastern Asia (n = 202), India (n = 185), Northern Europe (n = 126), Russia & Ukraine (n = 197), Southern Europe (n = 162), United States (n = 297). A principle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The strengths of the current study include the large study sample, which is the largest so far in the literature investigating the factor structure of the PANSS as well as efforts to clinically stage schizophrenia. In contrast to other studies, we did not exclude any basic component of the disease’s symptomatology (Kelley et al, 2013; Khan et al, 2013a, 2013b; Fong et al, 2015; Wu et al, 2015). An additional strength is the multi-center and multinational characteristic of the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of the current study include the large study sample, which is the largest so far in the literature investigating the factor structure of the PANSS as well as efforts to clinically stage schizophrenia. In contrast to other studies, we did not exclude any basic component of the disease’s symptomatology (Kelley et al, 2013; Khan et al, 2013a, 2013b; Fong et al, 2015; Wu et al, 2015). An additional strength is the multi-center and multinational characteristic of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the presence of significant associations of stage of illness with course, outcome, prognosis, and treatment response (Nakaya et al, 1999a, 1999b; Emsley et al, 2007; Cuesta et al, 2012; Hill et al, 2012). The effect of socio-cultural factors as well as intrinsic factors pertaining to the specific diagnostic and conceptual approaches of individual researchers and research centers could exert a major contributing effect towards significant heterogeneity of the results (Khan et al, 2013a, 2013b), but these issues are not adequately studied (Dollfus and Petit, 1995; Nakaya et al, 1999a, 1999b; Hayashi et al, 2002; Walsh-Messinger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also plausible that the translation of these items into Arabic did not capture the same construct provided in English versions or the raters showed variability on some of these items. In a study on crosscultural validity of the PANSS [41] among different countries, the authors suggested that differences in scoring, in addition to culture and translation, could also contribute to the differences in factor structures among cultures. Schizophrenia has been viewed initially to be very similar across cultures where the degree of the overlap in the illness definition and symptoms in many countries increases with the illness severity [6] .…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, to obtain valid measures of illness severity, it is essential that rating scales are both scalable and transferable. Although prior studies have evaluated some psychometric properties of the PANSS , the scalability and transferability of the full PANSS‐30 and the proposed PANSS‐14 and PANSS‐8 subscales have never been tested by means of the Rasch rating scale model.…”
Section: Introductionmentioning
confidence: 99%